The leishmanicidal effect of Lucilia sericata larval saliva and hemolymph on in vitro Leishmania tropica - Sara Rahimi; Ali khamesipour; Amir Ahmad Akhavan; Javad Rafinejad; Reza Ahmadkhaniaha; Mahmood Bakhtiyari; Arshad Veysi; Kamran Akbarzadeh (Parasites & Vectors, 2021)
Abstract Background Leishmaniasis is a major parasitic disease worldwide, except in Australia and Antarctica, and it poses a significant public health problem. Due to the absence of safe and effective vaccines and drugs, researchers have begun an extensive search for new drugs. The aim of the current study was to investigate the in vitro leishmanicidal activity of larval saliva and hemolymph of Lucilia sericata on Leishmania tropica. Methods The effects of different concentrations of larval products on promastigotes and intracellular amastigotes of L. tropica were investigated using the mouse cell line J774A.1 and peritoneal macrophages as host cells. The 3-(4.5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and direct observation and counting method were used to assess the inhibitory effects and cell cytotoxicity of the larval products. The effects of larval products on the amastigote form of L. tropica were quantitatively estimated by calculating the rate of macrophage infection, number of amastigotes per infected macrophage cell, parasite load and survival index. Results The 50% cytotoxicity concentration (CC50) value of both larval saliva and hemolymph was 750 µg/ml, and the 50% inhibitory concentration (IC50) values were 134 µg/ml and 60 µg/ml for larval saliva and larval hemolymph, respectively. The IC50 for Glucantime, used a positive control, was (11.65 µg/ml). Statistically significant differences in viability percentages of promastigotes were observed for different doses of both larval saliva and hemolymph when compared with the negative control (p ≤ 0.0001). Microscopic evaluation of the amastigote forms revealed that treatment with 150 µg/ml larval hemolymph and 450 µg/ml larval saliva significantly decreased the rate of macrophage infection and the number of amastigotes per infected macrophage cell. Conclusion Larval saliva and hemolymph of L. sericata have acceptable leishmanicidal properties against L. tropica.